Postural balance assessment in elderly practitioners of physical activity in different strata age Avaliação do equilíbrio corporal em idosas praticantes de atividade física segundo a idade - Pavanate A.A.* (2018)
© 2018 Colégio Brasileiro de Ciências do EsporteThe aim was to verify the relationship of body balance, according to age and groups of age in elderly women engaged in physical activity. Method: 130 elderly divided into four age groups: from 60 to 64 years (G1); 65‐69 (G2); 70‐74 (G3); and 75 to 79 (G4). For assessment was used the Timed Up and Go test (TUG), One Leg Stand (OLS) Sit back and Lift 5 times (CS5) and Functional Reach (FR). For statistical analysis, we used Spearman correlation and Kruskal‐Wallis. Results: There was a correlation between age and the TUG and AU tests. It showed a statistically significant difference in the TUG between G1 and G4 and for OLS, between G1 and G4 and G2 and G4. Conclusion: unger seniors have better performance in balance tests like TUG and OLS.